Immunology of cord blood T-cells favors augmented disease response during clinical pediatric stem cell transplantation for acute leukemia - Roisin Borrill; Roisin Borrill; Kay Poulton; Kay Poulton; Robert Wynn; Robert Wynn (Frontiers Media S.A., 2023)
Allogeneic hematopoietic stem cell transplantation (HSCT) has been an important and efficacious treatment for acute leukemia in children for over 60 years. It works primarily through the graft-vs.-leukemia (GVL) effect, in which donor T-cells and other immune cells act to eliminate residual leukemia. Cord blood is an alternative source of stem cells for transplantation, with distinct biological and immunological characteristics. Retrospective clinical studies report superior relapse rates with cord blood transplantation (CBT), when compared to other stem cell sources, particularly for patients with high-risk leukemia. Xenograft models also support the superiority of cord blood T-cells in eradicating malignancy, when compared to those derived from peripheral blood. Conversely, CBT has historically been associated with an increased risk of transplant-related mortality (TRM) and morbidity, particularly from infection. Here we discuss clinical aspects of CBT, the unique immunology of cord blood T-cells, their role in the GVL effect and future methods to maximize their utility in cellular therapies for leukemia, honing and harnessing their antitumor properties whilst managing the risks of TRM.